Pengawasan Tata Usaha di SMK Al-Hikmah Mesuji - Sari, Sindy Fatika; Febriyanti, Febriyanti; Zulkipli, Zulkipli (El-Idare, 2025)
The supervision of administrative affairs at SMK Al Hikmah Mesuji OKI plays a crucial role in ensuring the effectiveness and efficiency of school administration. This study aims to analyze the implemented supervision system, supporting factors, and challenges in managing administrative tasks. The research employs a qualitative descriptive method with data collection techniques including observation, interviews, and documentation. The findings indicate that supervision is systematically carried out through stages of standard setting, measurement, result comparison, and corrective actions. The Head of Administration actively monitors and provides guidance to staff, ensuring that school administration runs orderly and in accordance with established procedures. Supporting factors for supervision include staff motivation and competence, a conducive work environment, and support from the community and external parties. However, budget constraints pose a challenge in providing adequate facilities and infrastructure. Despite this, administrative staff continue to carry out their duties optimally through creative solutions and resource efficiency. In conclusion, the applied supervision system has had a positive impact on improving the efficiency and accuracy of school administration, thereby supporting overall operational smoothness.